1974
DOI: 10.1079/bjn19740003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A deficiency on protein catabolism in chicks

Abstract: 1. The changes in the concentration of some enzymes and their metabolites were studied in the first stages of vitamin A deficiency in chicks.2. Kidney arginase (EC3.5.3.1) and liver xanthine dehydrogenase activities had increased even before complete disappearance of vitamin A from the plasma. Similarly, an increase was found in plasma uric acid, and plasma urea also increased but to a lesser extent. Liver proteolytic activity also was slightly increased by vitamin A deficiency.3. Kidney D-amino acid oxidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Stoewsand and Scott (1959) only report plasma urate levels of 4.5-9 mg%, Bruckental et al (1974) about 9 mg% while Henk (1966) stated that there was a gradual rise between the first and seventh weeks and that birds with 22 mg% were very sick and those with 30 mg% never survived. Scott (1961) believed that in poults but not chicks the blood uric acid level could be used as a reliable indication of the severity of the deficiency.…”
Section: Vitamin a Deficiencymentioning
confidence: 94%
“…Stoewsand and Scott (1959) only report plasma urate levels of 4.5-9 mg%, Bruckental et al (1974) about 9 mg% while Henk (1966) stated that there was a gradual rise between the first and seventh weeks and that birds with 22 mg% were very sick and those with 30 mg% never survived. Scott (1961) believed that in poults but not chicks the blood uric acid level could be used as a reliable indication of the severity of the deficiency.…”
Section: Vitamin a Deficiencymentioning
confidence: 94%
“…At the age of 5 weeks, -A chicks, raised on a diet without vitamin A, manifested signs of severe avitaminosis A: their body-weight was about 60% of that of the controls and retinol was not detected in the liver. There was a considerable increase in serum uric acid in -A chicks, characteristic of avitaminosis A in birds (Bruckental et al 1974). The results also showed that -A chicks became Zn deficient.…”
Section: Development Of'avitaminosis a And Zn Dejciency In Chicksmentioning
confidence: 73%
“…The control group was given ad lib. the diet containing retinyl acetate (2752 pg/kg) added in oil to the basal diet in accordance with the recommended dosage (Bruckental et al 1974). The second group received the vitamin-A-free basal diet (-A chicks).…”
Section: Experimental Design a N D Methodsmentioning
confidence: 99%
See 1 more Smart Citation